The most promising microneedle device: present and future of hyaluronic acid microneedle patch - Huizhi Kang; Zhuo Zuo; Ru Lin; Muzi Yao; Yang Han; Jing Han (Taylor & Francis Group, 2022)
Microneedle patch (MNP) is an alternative to the oral route and subcutaneous injection with unique advantages such as painless administration, good compliance, and fewer side effects. Herein, we report MNP as a prominent strategy for drug delivery to treat local or systemic disease. Hyaluronic acid (HA) has advantageous properties, such as human autologous source, strong water absorption, biocompatibility, and viscoelasticity. Therefore, the Hyaluronic acid microneedle patch (HA MNP) occupies a large part of the MNP market. HA MNP is beneficial for wound healing, targeted therapy of certain specific diseases, extraction of interstitial skin fluid (ISF), and preservation of drugs. In this review, we summarize the benefits of HA and cross-linked HA (x-HA) as an MNP matrix. Then, we introduce the types of HA MNP, delivered substances, and drug distribution. Finally, we focus on the biomedical application of HA MNP as an excellent drug carrier in some specific diseases and the extraction and analysis of biomarkers. We also discuss the future development prospect of HA MNP in transdermal drug delivery systems (TDDS).